A Rice PECTATE LYASE-LIKE Gene Is Required for Plant Growth and Leaf Senescence . Issue 2 (28th April 2017) - Leng, Yujia; Yang, Yaolong; Ren, Deyong; Huang, Lichao; Dai, Liping; Wang, Yuqiong; Chen, Long; Tu, Zhengjun; Gao, Yihong; Li, Xueyong; Zhu, Li; Hu, Jiang; et al.
Abstract : DEL1 affects rice growth and leaf senescence mediated by PECTATE LYASE-LIKE genes. Abstract: To better understand the molecular mechanisms behind plant growth and leaf senescence in monocot plants, we identified a mutant exhibiting dwarfism and an early-senescence leaf phenotype, termed dwarf and early-senescence leaf1 ( del1 ). Histological analysis showed that the abnormal growth was caused by a reduction in cell number. Further investigation revealed that the decline in cell number in del1 was affected by the cell cycle. Physiological analysis, transmission electron microscopy, and TUNEL assays showed that leaf senescence was triggered by the accumulation of reactive oxygen species. The DEL1 gene was cloned using a map-based approach. It was shown to encode a pectate lyase (PEL) precursor that contains a PelC domain. DEL1 contains all the conserved residues of PEL and has strong similarity with plant PelC. DEL1 is expressed in all tissues but predominantly in elongating tissues. Functional analysis revealed that mutation of DEL1 decreased the total PEL enzymatic activity, increased the degree of methylesterified homogalacturonan, and altered the cell wall composition and structure. In addition, transcriptome assay revealed that a set of cell wall function- and senescence-related gene expression was altered in del1 plants. Our research indicates that DEL1 is involved in both the maintenance of normal cell division and the induction of leaf senescence. These findings reveal a new molecular mechanism for plant growth and leaf senescence mediated by PECTATE LYASE-LIKE genes.